Pathologic complete response after neoadjuvant therapy for locally advanced rectal cancer in a real-world setting: a population-based study - Cadili, Lina; Loree, Jonathan M.; Peacock, Michael; DeVries, Kimberly; Ghuman, Amandeep; Karimuddin, Ahmer A.; Phang, P. Terry; Raval, Manoj J.; Brown, Carl J. (Frontiers in Oncology, 2025)
AimThis study aimed to determine the impact of time from neoadjuvant therapy (NAT) to surgery on the complete pathologic response (pCR) rate in patients with locally advanced rectal cancer. NAT decreases the local recurrence of rectal cancer. Some patients achieve a pCR. The optimal time between NAT and surgery to maximize pCR remains uncertain.MethodWe identified adults with Tany, Nany, M0 rectal adenocarcinoma treated with short-course radiation therapy (SCRT) or long-course chemoradiotherapy (LCRT) followed by total mesorectal excision. Multivariable logistic regression examined characteristics associated with pCR and survival.ResultsIn total, 3,476 patients were included from between 2000 and 2017. Of these, 1,554 (44.7%) received LCRT and 1,796 (51.7%) SCRT. The pCR rate was 13.2% (181/1373) among the LCRT group and 1.5% (26/1770) among the SCRT group. A pCR among the SCRT group was positively associated with weeks from SCRT to surgery [odds ratio (OR) 1.45, 95% confidence interval (CI) 1.13,1.86; p=0.003], tumor grade (grade 1 OR 5.72, 95% CI 1.70, 19.30, p=0.005), and stage (stage 1 OR 7.07, 95% CI 2.49, 20.08, p=<0.001). The pCR rate among the LCRT group was not associated with weeks from LCRT to surgery but was associated with sex and stage. Median follow-up was 9.5 years, and median overall survival (OS) was 9.7 years. Among patients receiving LCRT, the 5-year OS rate was higher (69.8%) when surgery followed LCRT by 6–10 weeks compared to those undergoing surgery <6 weeks or 10+ weeks post-LCRT (p = .003).ConclusionAmong rectal cancers treated with LCRT in a population-based cohort, longer delay to radical resection is associated with increased pCR rate. However, the overall pCR rate was lower than that reported in trial populations.